The City of London and the Euro - Carine Berbéri (Hochschule Koblenz - University of Applied Sciences, Fachbereich Wirtschaftswissenschaften, 2014)
Analyzing the attitude of the City of London towards the euro can seem a bit strange today, at a time when Great Britain has still not joined the eurozone and even tries to organize a referendum about Britain's EU membership. One should not forget that in January 2013 Prime Minister David Cameron promised he would hold such a referendum if the Conservatives were re-elected in 2015. Nevertheless, examining the attitude of the City remains interesting insofar as it reflects the difficult relations between Britain and Europe / Britain and European monetary initiatives. As mentioned by Tony Blair in July 1999: "Yet, we always come back to the same dilemma: in or out of Europe. To be in or not to be in, that is the question. In the end, we have always chosen to be in" (Speech to the London Business School). Furthermore, one can wonder whether the City, which is one of the main business and financial centres in the world and the largest financial centre in Europe, has been much affected by Blair's decision not to join the euro in 1999. Focusing on the City seems all the more interesting today since the Cameron-Clegg government has increasingly tried to protect London's financial centre over the past European summits. Consequently, the purpose of this article is to study the impact of the euro on the City so as to examine whether London's position as a financial centre has been threatened since the late 1990s. It will also try to determine if the City has been influenced by the less and less constructive attitude of the Cameron-Clegg government towards the euro and the European Union (EU).
urn:nbn:de:hbz:1105-opus4-257
Keywords: 330; Finanzsektor; Eurozone; Großbritannien